@stephen.shore: an ongoing archive of seeing. (4th May 2021) - Reis, Cláudio
Abstract : Since 2014, photographer Stephen Shore has been exploring Instagram as a new body of work, having its own online portfolio entry next to iconic series as American Surfaces and Uncommon Places. Instead of joining contemporary debates concerning the crisis of representation implicit in the networked condition of the photographic image, Shore is keen to engage with Instagram through the lens of modernism, concentrating his attention on the visual characteristics intrinsic to photography as a medium, a reasoning previously encapsulated in the primer The Nature of Photographs. Building upon selected samples from Shore's pre-digital archive in addition to his most recent series, Details, the research takes @stephen.shore as a significant case study to examine how Instagram affects the modernist emphasis on seeing photographically the ordinary, evaluating the contemporary relevance of Shore's networked notational impulse when many Instagram users engage with photography to keep a quasi-diaristic practice. Looking at the traces of everyday life, envisaged for Instagram or the gallery wall, the camera is but a tool for reflecting upon a concept Shore long borrowed from the great writer T. S. Eliot: the "objective correlative", allowing for poetry to be found, and given visual structure.